(untitled) (Experimental biology, 2015)
Peptidoglycanhydrolases play an important role in Lactobacilli cells division and at the same time, have a significant effect on the immune status of the colonized organisms. Genes encoding peptidoglycanhydrolases of Lactobacillus rhamnosus GG p40 and p75 and their homologues are the objects of interest for cloning to enhance their expression in the homo- and heterologous background. The sequences of p40 and p75 homologues from strains Lactobacillus rhamnosus BSR and Lactobacillus casei BI005 were found using specific primers, and products of their amplification were cloned into the pGEM-T vector. The resulting plasmid constructions will be used for further manipulations to study the peptidoglycanhydrolases genes expression in E.coli cells.